Quarantine, physical distancing and social isolation measures in individuals potentially exposed to SARS-CoV-2 in community settings and health services: a scoping review - de Freitas, Tereza Brenda Clementino; Belo, Rafaella Cristina Tavares; Siebra, Sabrina Mércia dos Santos; Medeiros, André de Macêdo; de Brito, Teresinha Silva; Carrillo, Sonia Elizabeth Lopez; do Nascimento, Israel Junior Borges; Sakamoto, Sidnei Miyoshi; de Moraes, Maiara (Nepal Journal of Epidemiology, 2022)
To provide a synthesis of diverse evidence on the impact of the non-therapeutic preventive measures, specifically quarantine, physical distancing and social isolation, on the control of COVID-19. A scoping review conducted in the PubMed, Embase, LILACS, CENTRAL and SCOPUS databases between 2019 and August 28th, 2020. The descriptors used were the following: “quarantine”, “physical distancing”, “social isolation”, “COVID-19” and “SARS-Cov2”. Studies that addressed the non-therapeutic preventive measures in people exposed to SARs-CoV-2 in community settings and health services were included. A total of 14,442 records identified through a database search were reduced to 346 studies and, after a standardized selection process, a total of 68 articles were selected for analysis. A total of 35 descriptive, cross-sectional or longitudinal observational studies were identified, as well as 3 reviews, in addition to 30 studies with mathematical modeling. The main intervention assessed was social distancing (56.6%), followed by lockdown (25.0%) and quarantine (18.4%). The main evidence analyzed points to the need for rapid responses to reduce the number of infections, deaths and hospital admissions, especially in intensive care unit beds.The current review revealed consistent reports that the quarantine, physical distancing and social isolation are effective strategies to contain spread of the new coronavirus.